Capter l’autre. Ethnographie de l’univers connecté des gens du voyage - Gaëlla Loiseau (Netcom)
From 2010-2011, the use of social media has grown among nomadic people. While the media and political spheres re-activated stigmatization process against them, nomadic people were accessing to communication tools to eminent potential for emancipation and creation. This article aims to explore many facets of this appropriation of social media by marginalized population. We discover that it’s often through humour and language games that emerges a « nomadic » signature on the net.